Investigation and analysis of Ayatollah Javadi Amoli's view on "allegorical expression" and its relationship with "various types of analogy" - Ali Ali Modbar Islami; leyla salehi (حکمت اسرا)
Ayatollah Javadi Amoli, in his interpretation of some verses of the Qur'an in which a specific example is mentioned, considered the expression of the verse to be "allegory" regarding that example; not "determining and limiting" and as a result extends the ruling mentioned in the verse to similar cases. This kind of interpretation (interpretation of some expressions of the Qur'an as an allegory), while emphasizing the knowledge-giving and realistic nature of the Qur'an's expressions, causes a change in the commentator's view of the scope of the Qur'an's meanings and, consequently, causes explanations It will become a broader Qur'an about individual and social issues, and since the view of "allegorical expression" is synonymous with "various types of analogy", this article after analyzing this view, examines its relationship with the aforementioned concepts. And he reaches the conclusion that the ratio of allegorical expression with different types of analogy is as follows: 1. It is not a type of analogy, because in allegorical expression there is no explanation of the cause. 2. It is not different from the analogy of inferential inference with definite inference, that is, the same analogy with the induction of particularity and refinement of definite manat. 3. It has nothing to do with hypothetical analogy (al-inferential analogy with hypothetical inference and analogy with the induction of particularity and revision of hypothetical manat).